Rancang Bangun Sistem Informasi Digitalisasi UMKM Kuliner Berbasis Web sebagai Media Promosi dan Pengelolaan Usaha - Fathin Ryfsa Fadilah; Eko Purwanto; Aprilisa Arum Sari (Fakultas Teknik Universitas Hamzanwadi, 2026)
This research aims to design and develop a web-based information system for culinary MSME merchants to support the digitalization of promotion and business information management in a more effective and integrated manner. The existing problem is that data management and culinary information dissemination are still conducted manually, causing information related to shelters, food and beverage menus, and merchant data to be delivered less optimally to the public. The system development method used in this research is the Waterfall method, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using the Laravel framework and MySQL database, while Unified Modeling Language (UML) was utilized as a system modeling tool. The system provides three access levels, namely admin, seller, and buyer, to support MSME data management, menu management, and centralized culinary information services. This study used 10 shelters as implementation testing data from approximately 120 available shelters. The testing results indicate that the system functions properly and assists users in accessing culinary information more quickly, effectively, and efficiently. The developed web-based system is expected to enhance culinary MSME promotion and support digital transformation in culinary business management.